Collaborative Intervention Assistance Model In An Effort To Increase The Quality Of Pregnant Women Services To Reduce Maternal Mortality In Padang City - Adnani, Syahredi; Rizanda Machmud; Dwiana Ocviyanti (Fakultas Kedokteran Universitas Andalas, 2024)
Background : Maternal death, as defined by WHO, includes deaths during pregnancy or within 42 days postpartum due to pregnancy-related causes. The Maternal Mortality Rate (MMR) quantifies maternal deaths per 100,000 live births. A key target of the Millennium Development Goals (MDGs) was reducing the MMR by three-quarters between 1990 and 2015, aiming for a global rate under 70 per 100,000 by 2030. In Indonesia, the 2012 Demographic and Health Survey reported an MMR of 359 per 100,000 live births, with West Sumatra at 212 per 100,000. Objective : This study employs a mixed-method approach, focusing on pregnant women visiting health centers in Padang City, to assess an intervention model. Result : Maternal mortality in Indonesia is mainly caused by bleeding, eclampsia, and infections, with contributing factors including delayed care access, socio-cultural, educational, and economic challenges. Significant health issues include hypertensive disorders, diabetes, acute kidney injury, jaundice, and thyroid disease. Low educational and economic levels in rural areas correlate with higher maternal morbidity and mortality. Government efforts, such as the Maternity Guarantee (Jampersal) and the Maternal and Child Health (KIA) Handbook, aim to improve maternal health but face challenges due to poor resource utilization. Conclusion : Indonesia struggles to meet maternal mortality reduction targets, with rates high compared to other Asian countries. Effective interventions must address both direct and indirect causes of maternal deaths, improve education and economic conditions, and enhance healthcare access. Government programs show promise but require better implementation and community engagement to reduce maternal mortality rates effectively.